Fur seal arbitration, in the matter of the claims of Great Britain against the United States of America before the Bering Sea Claims Commission [electronic resource] : argument for the United States in reply. (Washington : G.P.O., 1897)
Electronic reproduction. Mode of access: Internet. 44